Inhibition of Experimental Age-Related Macular Degeneration by ZQMT in Mice - Yang, Liu; Meng, Huan; Luo, Dan; Deng, Tingting; Miao, Li; Zou, Bin; Ge, Xiaofei; Hu, Xiao; Liu, Yu; Li, Xifang; Deng, Xiuli; Guo, Shixin; et al. (Current Molecular Medicine, 2019)
Background: Age-related macular degeneration (AMD) is a progressive and irreversible eye disease. The anti-vascular endothelial growth factor (VEGF) therapy has revolutionized the treatment of neovascular AMD. However, the expense for such treatment is quite high. Methods: We used a traditional Chinese medicine ZQMT as an alternative therapeutic regimen for AMD. We employed two in vivo animal models mimicking dry and wet AMD respectively to assess the therapeutic efficacy of ZQMT on treating AMD-related retinopathy. AMD-related retinopathy in Crb1rd8 mice was evaluated from week 1 to 8 by fundus photography. Laser-induced choroidal neovascularization (CNV) was evaluated by fluorescein angiography and histopathology. Results: ZQMT increased CX3CR1 expression in murine CD4+ T cells either cultured in vitro or directly isolated from animals treated with ZQMT. We also performed both in vitro and in vivo studies to confirm that ZQMT has no apparent toxic effects. ZQMT alleviated AMD-related retinopathy in both Crb1rd8 and CNV models. Depletion of CCL2 and CX3CR1 in Crb1rd8 mice abolished the efficacy of ZQMT, suggesting that CCL2 and/or CX3CR1 may underlie the mechanisms of ZQMT in treating AMD-related retinopathy in mice. Conclusion: In summary, our study supports the protective roles of a traditional Chinese medicine ZQMT in AMD.
Keywords: CX3CR1